Partial differential equations - Taylor, Michael Eugene 1946- (Applied mathematical sciences, 1997)
This book is addressed to graduate students in mathematics and to professional mathematicians, with an interest in partial differential equations, mathematical physics, differential geometry, harmonic analysis, and complex analysis